1988
DOI: 10.1021/ie00084a012
|View full text |Cite
|
Sign up to set email alerts
|

Single-particle biomass pyrolysis: correlations of reaction products with process conditions

Abstract: Single, thermally thick particles of lodgepole pinewood were pyrolyzed under well-defined conditions of industrial importance. Particle thickness, heating level, moisture content, density, and grain axis relative to one-dimensional heating were varied using a Box-Behnken experimental design. Gross product fractions, as well as components therein, were measured and the batch yields were correlated with second-order polynomials. The empirical equations correlating the batch yields, together with their prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
1
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 23 publications
(35 reference statements)
7
48
1
1
Order By: Relevance
“…This is because, when the biomass particle size increases, the distance from the biomass particle's surface to its centre increases, which delays the heat transfer rate from the hot material to cold biomass. Therefore, the bio-oil yield decreases [22]. Figure 2.…”
Section: Pyrolysis Processmentioning
confidence: 99%
“…This is because, when the biomass particle size increases, the distance from the biomass particle's surface to its centre increases, which delays the heat transfer rate from the hot material to cold biomass. Therefore, the bio-oil yield decreases [22]. Figure 2.…”
Section: Pyrolysis Processmentioning
confidence: 99%
“…The shrinkage of biomass in pyrolysis has also been studied both experimentally [25,26] and numerically [27][28][29][30]. The results have shown that both primary and secondary reaction paths are affected by the shrinkage of the char layer, and larger tar yields are predicted for shrinking particles.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal conductivity across and tangential to the grain direction is approximately one third that along the grain [8]. Also, the permeability to gas flow across the wood grain is much lower than that along the other two directions [8] (up to a factor of lo4). To study the effects of wood anisotropy on the thermal degradation, different properties along the x and y directions are assigned.…”
Section: Mathematical Formulation Of the Problemmentioning
confidence: 90%
“…From the physical point of view, the model here presented describes the transport phenomena occurring through the cross section of a wooden sample exposed in a pre-heated, inert atmosphere furnace. Wood is an anisotropic material with different properties along, cross and tangential to the grain [8]. Thermal conductivity across and tangential to the grain direction is approximately one third that along the grain [8].…”
Section: Mathematical Formulation Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation